(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Both the literary universe that constitutes José Lezama Lima’s work, and his personal poetic theory have been studied in several ways and from different points of view. However, because of the magnitude and cryptic character of these aspects, there are many elements that have not been discussed yet. One such case is the animal universe that pervasively appears in Lezama’s texts. This study focuses on the three animals that are included most frequently in this Cuban writer’s poetry books.